2017
DOI: 10.3390/su9040527
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Balanced Scorecard (BSC), Strategy Map, and Fuzzy Analytic Hierarchy Process (FAHP) for a Sustainability Business Framework: A Case Study of a Spanish Software Factory in the Financial Sector

Abstract: This paper presents a case study of how a Spanish financial software factory (FSF) has determined the weights of the indicators and objectives included in their strategy map with the aim of ensuring its business sustainability. A strategy map is a graphical representation of the cause-effect relationships between strategic objectives and indicators of a balanced scorecard (BSC). The detailed description of the strategy map development and deployment is not part of the aim of this work as it was described in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 61 publications
0
11
1
Order By: Relevance
“…Based on the analysis, the study confirmed that mediating effects are integral to strategy maps and that the direct and indirect effects could potentially provide a deeper understanding of how these perspectives are linked to one another. Unlike other studies (Pérez et al 2017;Valmohammadi and Sofiyabadi 2015;Wu 2012), which focus on giving weight to perspectives or highlighting the most important perspective in a strategy map, this study shows that organizations should not ignore any of the causal relationships between the four perspectives.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Based on the analysis, the study confirmed that mediating effects are integral to strategy maps and that the direct and indirect effects could potentially provide a deeper understanding of how these perspectives are linked to one another. Unlike other studies (Pérez et al 2017;Valmohammadi and Sofiyabadi 2015;Wu 2012), which focus on giving weight to perspectives or highlighting the most important perspective in a strategy map, this study shows that organizations should not ignore any of the causal relationships between the four perspectives.…”
Section: Discussioncontrasting
confidence: 66%
“…To prioritize the perspectives incorporated into the BSC strategy map, Pérez et al (2017) employed the Fuzzy Analytic Hierarchy Process (FAHP) analysis to create a weighted strategy map. Based on a case study of a software factory that employed FAHP to determine the weights for BSC measures and KPIs, their results suggest that the factory focused primarily on the customer perspective and that customer satisfaction was the most important KPI used to evaluate performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By knowing the importance rank of different perspectives (e.g., financial, customer, internal business processes, learning and growth) and related key performance indicators (e.g., cost structure, reduction of cost, user satisfaction, cost per use, performance, productivity, delays, quality, budgeting, etc. ), the strategic line of the company may establish priorities and design the process-based model to improve productivity and cost performance [18,19].…”
Section: Sustainable Development and Business Implicationsmentioning
confidence: 99%
“…What can be helpful is a responsibility account which holds managers accountable for the effects of their business entity's sustainable development activities. Such an account must be supported by instruments which integrate financial and non-financial information, including Activity Based Responsibility Accounting, Sustainable Balanced Scorecard, and Activity-and Strategy-Based Responsibility Accounting (e.g., [70][71][72][73][74][75][76]). Before these tools can be applied, more in-depth research into institutional theory perspective is required regarding the possibilities of designing and using such tools to measure the economic, social and environmental potential of a socially responsible business, and to anticipate how it is going to change in the long run.…”
Section: The Author's Concept Of Sustainable Management Accounting Asmentioning
confidence: 99%